Anti-Glioblastoma Activity of Alkaloids from Annona Cherimola Mill.: Network Pharmacology, Molecular Docking and in Silico Analysis (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Glioblastoma, also known as Glioblastoma multiforme (GBM), is the most aggressive type of cancer that originates in the brain. Annona cherimola is an Indian medicinal plant with antioxidant, antidiabetic, antimicrobial, antitumor, antianxiety and antiparasitic activities. In this study, we examined the anti-glioblastoma potential of alkaloids from A. cherimola using computational approach. The phytochemicals were obtained from IMPPAT and the Coconut database. SwissADME, ProTox 3.0 and CardioTOXCSM web servers were used to estimate the physicochemical, pharmacokinetic and toxicological profiles; the results demonstrated the druggable nature of the compounds. The OSIRIS Property Explorer evaluated the drug score, and Network pharmacology analysis predicted the appropriate targets of the phytochemicals. Molecular docking was performed with MZ-Dock in Autodock Vina mode and visualised with PyMol. The results clearly indicated that the phytochemicals would be quite effective against Glioblastoma via targeting PIK3CA and EGFR. The molecular docking study revealed that all the compounds displayed better binding energy and interaction profile against the chosen targets, and the results were compared with the co- crystallised ligand. Owing to the various in silico studies, molecular docking and drug score, the compounds (+) – nornantenine, Artabotnaine, Corytuberine, Lanuginosine, Liriodenine and Lysicamine were highly active against the tested targets. Thus, these compounds can be used against Glioblastoma. However, further in vitro and in vivo studies are warranted.
Keywords: Glioblastoma; Annona cherimola Mill; Computational studies; Network Pharmacology; Molecular docking